2020
DOI: 10.3390/su12187362
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Disruption in Management and Education Academics: Bibliometric Mapping and Analysis

Abstract: COVID-19, What to do now? This issue has had devastating effects in all domains of society worldwide. Lockdowns, the lack of freedom and social distancing meant the closure of a country’s entire activity. Having effects at all levels, beside incalculable ones in health, it is argued that scientific activity in education, business, economics and management suffered some of the most drastic impacts of this pandemic. This study aims to map the scientific literature in these areas in the context of COVID-19 and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 132 publications
2
50
0
3
Order By: Relevance
“…Findings obtained within the study, Aristovnik et al, (2020), Chen, Huang, et al (2020), Fan et al (2020) With the findings obtained in the studies carried out by Kaya and Erbay (2020), the pandemic shows similarities in terms of identifying keywords. Nevertheless Rodrigues et al (2020) similar to the majority of the findings obtained in the study.…”
Section: 33%supporting
confidence: 91%
“…Findings obtained within the study, Aristovnik et al, (2020), Chen, Huang, et al (2020), Fan et al (2020) With the findings obtained in the studies carried out by Kaya and Erbay (2020), the pandemic shows similarities in terms of identifying keywords. Nevertheless Rodrigues et al (2020) similar to the majority of the findings obtained in the study.…”
Section: 33%supporting
confidence: 91%
“…The studies chosen for the analysis were found to be of various typologies, the most relevant of which was qualitative. The analysis revealed that research on the disruption in education and scientific production caused by the pandemic is rather scarce, which might be the result of the lack of empirical data (Rodrigues et al, 2020).…”
Section: Related Workmentioning
confidence: 99%
“…The pandemic emerged quickly leaving academics feeling stressed, unsure, and unprepared for what was ahead (Rodrigues et al, 2020). There were instances where staff were directed by the university to take an approach which was contradicted shortly thereafter.…”
Section: Communication Is Key In Emergent Situationsmentioning
confidence: 99%